2021
DOI: 10.1080/21505594.2021.1939608
|View full text |Cite
|
Sign up to set email alerts
|

Too young to die? How aging affects cellular innate immune responses to influenza virus and disease severity

Abstract: Influenza is a respiratory viral infection that causes significant morbidity and mortality worldwide. The innate immune cell response elicited during influenza A virus (IAV) infection forms the critical first line of defense, which typically is impaired as we age. As such, elderly individuals more commonly succumb to influenza-associated complications, which is reflected in most aged animal models of IAV infection. Here, we review the important roles of several major innate immune cell populations in influenza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 217 publications
(343 reference statements)
0
2
0
Order By: Relevance
“…ALF contains innate soluble components with the primary role of maintaining proper pulmonary function ( Notter, 2000 ; Fronius et al, 2012 ; Torrelles and Schlesinger, 2017 ). Our studies and others indicate that lung tissue in the elderly (in humans and mice) has a high basal inflammation and oxidative stress that leads to dysfunction of critical innate soluble and cellular components that could drive host susceptibility to respiratory infections and diseases [e.g., influenza, pneumonia, tuberculosis (TB)] ( Toapanta and Ross, 2009 ; Shivshankar et al, 2011 ; Canan et al, 2014 ; Moliva et al, 2014 ; Piergallini and Turner, 2018a ; Keilich et al, 2019 ; Bulut et al, 2020 ; Harpur et al, 2021 ). Thus, defining when and how these changes occur at the cellular and molecular level is critical to understand age-associated lung-specific pathologies and aging in general.…”
Section: The Lung Alveolar Environment During Agingmentioning
confidence: 79%
“…ALF contains innate soluble components with the primary role of maintaining proper pulmonary function ( Notter, 2000 ; Fronius et al, 2012 ; Torrelles and Schlesinger, 2017 ). Our studies and others indicate that lung tissue in the elderly (in humans and mice) has a high basal inflammation and oxidative stress that leads to dysfunction of critical innate soluble and cellular components that could drive host susceptibility to respiratory infections and diseases [e.g., influenza, pneumonia, tuberculosis (TB)] ( Toapanta and Ross, 2009 ; Shivshankar et al, 2011 ; Canan et al, 2014 ; Moliva et al, 2014 ; Piergallini and Turner, 2018a ; Keilich et al, 2019 ; Bulut et al, 2020 ; Harpur et al, 2021 ). Thus, defining when and how these changes occur at the cellular and molecular level is critical to understand age-associated lung-specific pathologies and aging in general.…”
Section: The Lung Alveolar Environment During Agingmentioning
confidence: 79%
“…In recent times, studies have shown that many countries, especially the Sub-Saharan countries and some parts of Europe, including Spain, lack knowledge of the One Health approach to tackle zoonotic infections, which leads to greater vulnerability in the spread of infections and outbreaks, for example, avian influenza A, and setbacks in reducing the spread of these diseases among community members and in the ecological system at large. Using a One Health approach, zoonotic diseases can be prevented from occurring, and if they do occur, the administration of good treatment to both the infected animals and human beings can promote health in animals, humans, and environmental life 8 .…”
Section: Main Textmentioning
confidence: 99%